Performance of W-1%Y2O3-0.5%Ti Plasma-Facing Composite Under Fusion Relevant Transient Heat Flux. (19th May 2021) - Li, Changjun; Zhu, Dahuan; Li, Xiangbin; Chen, Junling
Abstract: The W-1%Y2 O3 -0.5%Ti composite fabricated by the spark plasma sintering method has been tested on the EMS-60 facility using 0 to 600 MW/m 2 with pulse duration of 5 ms for single and 100 cycles. It is shown that the cracking threshold under single pulse of the W-1%Y2 O3 -0.5%Ti is close to 300 MW/m 2, which exceeds that of pure tungsten ( 200 MW/m 2 ) . Moreover, the crack morphology is different than that of pure W under the same heat load condition. These experimental data illustrate that the addition of dispersed oxides and alloying elements can, to some extent, ameliorate high heat load behaviors . Meanwhile, it should be noted that the melting and volatility of the second phase if the heat flux exceeds 400 MW/m 2 for a single pulse will narrow the operation range of the composite. And, the severe damages of crack and matrix melting under fatigue shocks illustrate that the composite still needs further efforts to be improved by the optimization of fabrication processing.